Novel [18F]-labeled thiol for the labeling of Dha- or maleimide-containing biomolecules - Mylène Richard; Françoise Hinnen; Bertrand Kuhnast (SpringerOpen, 2022)
Abstract Background Prosthetic approach for the radiolabeling of biologics with fluorine-18 is a robust strategy and has been employed for many years. It requires fast, biocompatible and selective reactions suited to these fragile molecules. Michael addition of a nucleophilic thiol moiety on α,β-unsaturated carbonyl entities is an interesting compromise between simplicity of preparation of the prosthetic reagent and control of the selectivity of the addition. The α,β-unsaturated carbonyl entity of the biologic can easily be generated by addition of a maleimide function using adequate heterobifunctional linkers or generated by selective modification of a cysteine residue leading to a dehydroalanine moiety. We report here the design, synthesis and radiosynthesis of a new fluoropyridine-based thiol [18F]FPySH and its conjugation via Michael addition on model dehydroalanine- or maleimide-containing biologics. Results The preparation of cold reference and labeling precursor of [18F]FPySH was achieved and its radiosynthesis was fully automated, enabling production of the thiol prosthetic group with a 7 ± 2.1% radiochemical yield after two steps. The conjugation of [18F]FPySH to two model Dha-containing molecules was then carried out in reducing conditions, yielding the corresponding adducts in 30-45 min reaction time. Furthermore, [18F]FPySH was employed to radiolabel the maleimide-modified c(RGDfK) peptide, affording the radiofluorinated analogue in 15 min. Conclusion We have developed an original [18F]-labeled thiol for site-selective conjugation and radiolabeling of Dha or maleimide-containing biomolecules of interest. Labeling of three model compounds was successfully carried out and gave the expected radiofluorinated adducts in less than 45 min, thus compatible with fluorine-18 half-life.